Public offices in processes of constitutional development - ALLEN, J.G. (Institutional Knowledge at Singapore Management University, 2024)
What factors drive constitutional change and sustain positive transformation? How are democratic values recognised, restored, and preserved through constitutional change? How can these questions be answered in a manner that is relevant to most of the world? This collection brings together leading and emerging scholars and practitioners to explore the relationship between democratic consolidation and constitutional endurance through consideration of recent experiences in seven African and Asian states that have undergone an understudied democratising event in the past decade: Ethiopia, The Gambia, Malaysia, Maldives, Myanmar, Sri Lanka, and Thailand. Building on the empirical surveys, seven thematic chapters offer analytical insights on seven themes arising from the case studies: the concept of ‘office’ and its relationship to political and constitutional development; the role of governing institutions in these processes of development; the roles played by political parties, which depart from established dominant ‘Western’ frameworks of thinking; the curious, diverse, and often marginal place of courts in the case studies; the often central importance of civil–military relations, which manifests in highly diverse ways; the salience and explanatory power of constitutional culture; and the impact of the COVID-19 pandemic. More broadly, the collection proposes a decolonising approach to comparative constitutional law and democratisation studies by reflecting on the linkages between methodology, collaboration, and community-building in a human-centred praxis of comparative enquiry.